2012
DOI: 10.4068/cmj.2012.48.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Cysteinyl Cathepsins: Multifunctional Enzymes in Cardiovascular Disease

Abstract: Until recently, the role of lysosomal cysteine protease cathepsins in intracellular protein degradation was believed to be mainly restricted to scavenging. However, recent studies have revealed nontraditional roles for cysteine protease cathepsins in the extracellular space during the development and progression of cardiovascular disease. Although the precise mechanisms are unknown, data from animal studies suggest that members of the cathepsin family, like other extracellular proteases, contribute to extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 86 publications
0
15
0
Order By: Relevance
“…Interestingly, expression of both cathepsin S and B has been well documented at inflammatory sites in various disease models including pancreatitis (39), inflammatory bowel disease (40), and atherosclerosis (41). It seems plausible that cathepsin-mediated cleavage of Rip1 kinase could play a role in perpetuating macrophage survival and function within inflammatory sites.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, expression of both cathepsin S and B has been well documented at inflammatory sites in various disease models including pancreatitis (39), inflammatory bowel disease (40), and atherosclerosis (41). It seems plausible that cathepsin-mediated cleavage of Rip1 kinase could play a role in perpetuating macrophage survival and function within inflammatory sites.…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsins are released by endothelial cells that sense and respond to TNF‐α (Keegan et al ., ). The serum levels of cathepsins are associated with inflammatory cytokine levels in patients with cardiovascular diseases (Li et al ., ). However, it was recently reported that cathepsin V, which is specifically expressed in humans (Zhou et al ., ), increases the expression of the inflammatory cytokine TNF‐α in macrophages (Pribis et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Cathepsin L (CatL), Cathepsin S (CatS), and Cathepsin K (CatK) release proteases to degrade extracellular collagen and elastin in the arterial wall, thus promoting atherogenesis [5]. Furthermore, cysteinyl Cats may have certain biological roles and molecular functions in vascular pathological processes, and may hence have potential application as diagnostic or prognostic markers [6]. Additionally, atherosclerotic lesions demonstrate an increased expression of chemokines such as chemotactic protein-1 (MCP-1), soluble vascular cell adhesion molecule-1 (sVCAM-1), and soluble E-selectin (sE-selectin) in endothelial cells of plaque microvessels or in endothelial cells overlying the lipid core-a response that may contribute to further leukocyte recruitment to sites of atherosclerosis [7].…”
Section: Introductionmentioning
confidence: 99%